Measurement of Cost & Benefit for Implementation of Risk Management in the Production Process - Muhammad Rosiawan; Moses Laksono Singgih; Erwin Widodo (IPTEK Journal of Proceedings Series, 2019)
The paper aims to measure the overhead costs and economic benefits of risk management activities in the production process - a manufacturing company. This research uses Activity Based Management (ABM) approach to allocate and track overhead costs in risk management activities. The overhead costs of risk management activities include the costs of identifying, analyzing, evaluating and controlling risks in order to achieve the quality objectives of the production process. The company obtains economic benefits, first, from reducing overhead costs incurred per period from the results of improvements to non-value-added or high-cost activities; second, cost savings obtained from the achievement of quality objectives per period. The results of this study indicate that the ABM approach used is appropriate in measuring the overhead costs and economic benefits of risk management activities in a business process